Defining and Practicing Reciprocity in Hazards and Disaster Research - Jessica Austin; Candace M. Evans; Jocelyn West; Heather Champeau; Lori Peek; Rachel M. Adams (International Journal of Qualitative Methods)
There is growing recognition of the importance of reciprocity between researchers and those involved in or affected by research, especially in sensitive field contexts such as disaster settings. Minimal applied guidance exists for researchers about how to practice reciprocity, however, resulting in several questions that have yet to be explored: What are the key considerations for practicing reciprocity in research? What potential unintended consequences should researchers be aware of when engaging in reciprocity? What practical strategies can help prepare researchers to engage in reciprocity and address challenges as they arise? Based on a systematic literature review—reflecting the shift of recent conceptions of reciprocity from transactional to more relational approaches—we offer a new, unifying definition of reciprocity as “an ongoing practice of critical reflection, relationship building, and exchange in which researchers are obligated to strive to produce mutual benefits for the people involved in or affected by the research process.” To motivate the practice of reciprocity, we highlight three key benefits: cultivating trust, addressing power imbalances, and improving research relevance. Additionally, through qualitative analysis of 53 research reports, we develop a typology of reciprocity in hazards and disaster research that clarifies six specific forms reciprocity can take, including: (1) centering participants and communities; (2) being empathetic and mindful of participant diversity; (3) sharing research results; (4) improving research and research team processes; (5) supporting learning, career development, or institutions; and (6) offering compensation. Finally, we outline potential challenges to practicing reciprocity and conclude with practical strategies for enhanced ethical grounding and effectiveness.